Rotating flow of nanofluid due to exponentially stretching surface: An optimal study. (October 2019) - Mohyud-Din, Syed Tauseef; Hamid, Muhammad; Usman, Muhammad; Kanwal, Afshan; Zubair, Tamour; Wang, Wei; Nazir, Aqsa
In this article, the presented study is based on a modification in Gegenbauer wavelets method. The modeled problem is presented to analyze the phenomena of transfer of heat of rotating nanofluids in which the flow is produced by an exponentially stretching sheet. The purpose of this study is to examine the simultaneous effects of rotation of nanofluid and exponentially stretching on the shear stresses and heat transfer rate, cooling proficiency of water-based nanofluids containing Ag, Cu, Al2 O3, TiO2, and CuO nanoparticles, and modification in Gegenbauer wavelets method to obtain the numerical solution of the said problem. A comparative analysis is presented among the outcomes obtained by modified Gegenbauer wavelets method, Runge–Kutta method of order-4, and already existing methods. The comparison shows that this modification is extremely efficient, and proposed technique could be extended for other physical problems.